Growth Performance and Economic Traits of Pigs Fed Diets Containing Either Normal Maize or Obatanpa - A Quality Protein Maize (Journal of Science and Technology, 2016)
Three diets containing either normal maize (CONTROL) or Obantapa (OBAT-I AND OBAT-II) – a quality protein maize – supplemented with decreasing amounts of fishmeal (14, 12, and 10% respectively) were fed ad libitum to a total of 15 individually-housed Large White pigs from a liveweight of 14 to 70kg. Mean feed intake and growth performance data were similar (p>0.05) for pigs on all the 3 dietary treatments. However in terms of feed cost/kg liveweight gain, diets containing Obantanpa are preferred because of the tendency of lower costs due to lower levels of inclusion of fishmeal. The carcass traits of the pigs fed the three diets were also similar (p>0.05). It was concluded that Obatanpa is nutritionally superior to normal maize and would help to reduce the cost of feeding pigs.